TASAWUF PENDIDIKAN: DARI SPIRITUALITAS MANUSIA MENUJU INSAN KAMIL - Ahmad Hanani; Nur Hamidi (Jurnal Pendidikan Agama Islam, 2019)
This article examines the relation and position of human beings in the context of "educational mysticism". This study using the literature approach to descriptive conceptual research to see the position of man as a creature of God specifically created by God and for certain purposes. Humans according to mysticism are creatures of God that are specially created ("copy") by God and for the purpose of His tajalli (tanazul) and because humans have the potential of the lut because of certain temptations he can glide to a low level, if he wants to return to his fitrah, then he should make a certain effort (mujahadah and riyadlah) in order to climb (taraqi) again "unite" with Him throughthe fourstages of tajalli. That tajalli, both in the process of tanazul and taraqqi, should be understood figuratively and metaphorically (majazi). Thus, a compromise can be made between the concept of Sufism al-Shafi, namely Sufism which combines Sufic vision with a vision of philosophy and Sunni Sufism, namely Sufism which assumes itself to the Koran and Al-Hadist.